A Capability Approach: Its Potential for Transformative Education Research Focusing on Education for Sustainable Development and Gender Issues in Science Teacher Education - Charles Chikunda (Environmental Association of Southern Africa, 2013)
In this article, I use the capability approach to explore the role that the science, mathematics and technical subjects (SMTs) teacher education curriculum can play as a 'gender conversion factor'. This comes amidst evidence that a major hindrance to the participation of girls in these disciplines is a lack of gender responsiveness in the pedagogy applied in schools. Seven teacher educators, who were purposively sampled at a Technical Teachers' College in Zimbabwe, were the research participants. I adopted a case study design in which I used in-depth interviews, focus-group discussions and document analysis to generate data. Data was analysed deductively using predetermined themes based on an analytical tool anchored on Sen's two, but quite distinct, aspects of freedom, that is, the opportunity aspect and the process aspect of freedom. The findings reveal that there is a limited awareness of gender issues among teacher educators, and that these issues are not being transformed into curriculum practice. All in all, it is evident that curriculum practices of SMTs teacher educators are riddled with gender blindness and so trainee teachers graduate from college without the necessary agency to deal with personal, social and environmental conversion factors that can play a role in girls converting the curriculum into functionings (beings and doings) and wider freedoms and valued beings and doings (capabilities).